An Approach to Long-Term Fiscal Policy Analysis - N'Diaye, Papa.; Dunaway, Steven (Washington, D.C. : International Monetary Fund, 2004)
This paper proposes an approach to setting fiscal policy that factors in the longer-term budgetary pressures that countries face owing, in particular, to population aging and rising health care costs. The approach attempts to overcome the difficulties in evaluating economic trade-offs and social welfare over extended periods. Long-term fiscal projections from the "Intergenerational Report" published as part of the Australian budget in May 2002 are used in a simple model of the Australian economy to illustrate some of the longer-term trade-offs that need to be considered in framing budgets over the medium term. These illustrative simulations, in particular, point out the importance of smoothing fiscal adjustment over time and, hence, the need for careful planning. Smoothing fiscal adjustment, however, raises a new set of questions regarding burden sharing across generations and what costs should be shared.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet